Analysis on Improving Utilization of Uranium Resource Based on Fast Reactor with Closed Fuel Cycle - HU Yun;YANG Yong;SONG Yingyun;YANG Peng (Yuanzineng kexue jishu, 2023)
Fast reactor combined with closed fuel cycle can greatly improve the utilization rate of uranium resource, get rid of the dependence of nuclear energy development on natural uranium, and meanwhile, reduce the generation of long-lived radioactive waste, so as to achieve environmental friendliness for nuclear energy. Using fast reactor to improve uranium resource utilization requires the recovery of spent fuel and multiple recycling of the recovered uranium and plutonium in fast reactors. Through neutronics and fuel burnup calculation, the characteristics of industrial plutonium multi-recycled in large MOX (mixed uranium and plutonium oxide) fuel sodium cooled fast reactor were simulated, the variation law of plutonium isotope component in the recycle process was obtained, and the feasibility of multiple recycling of plutonium in fast reactor was analyzed. The calculation results show that the plutonium isotope component can reach the equilibrium state along multiple recycling, and the fraction of fissile isotopes is maintained at a high proportion of about 74%. In terms of isotope composition quality, the number of recycling of industrial plutonium in fast reactor is not limited. An analysis model of uranium resource utilization rate was constructed. The improvement of uranium resource utilization rate of fast reactor with closed fuel cycle was calculated and analyzed, by using reactor core parameters of large-scale MOX fuel fast reactor, and the sensitivity analysis of uranium utilization rate to fuel burnup, spent fuel reprocessing recovery rate and reactor core breeding ratio was carried out. Under the strategy of fast reactor with closed fuel cycle, the utilization rate of uranium resource can be greatly improved after multiple recycling of recovered uranium and plutonium. Improving discharged fuel burnup and recovery rate of spent fuel reprocessing can significantly improve uranium utilization rate. However, in the first few cycles, fuel recovery rate has a small impact, while the utilization rate will be significantly improved after the number of recycles increases. In case of lower fuel burnup and recovery rate, there will be a lower upper limit on uranium utilization rate even with of infinite recycling numbers. The reactor core breeding ratio has less impact on the utilization rate of uranium resources. Theoretically, multiple recycling of recovered uranium and plutonium in fast reactor can achieve higher goal of uranium resource utilization rate, for example 60%, but under the lower fuel burnup and spent fuel reprocessing recovery rate, it will take more recycles (such as more than 30) to achieve the target. In order to reduce the number of recycles required (such as reduced to about 10) and further reduce recycle cost, improving fuel burnup and recovery rate of spent fuel reprocessing are important goals for the development of advanced nuclear energy systems with fast reactor and closed fuel cycle in the future.